Voltage-Induced Modulation of the Magnetic Exchange in Binuclear Fe(Iii) Complex Deposited on Au(111) Surface - Cardenas-Jiron, G (Royal Society of Chemistry, 2024)
We present a complete computational study devoted to the deposition of a magnetic binuclear complex on a metallic surface, aimed to obtain insight into the interaction of magnetically coupled complexes with their supporting substrates, as well as their response to external electrical stimuli applied through a surface-molecule-STM molecular junction-like architecture. Our results not only show that the deposition is favorable in two of the four studied orientations, but also, that the magnetic coupling is only slightly perturbed once the complex is adsorbed. We observe that the effects of the applied bias voltage on the magnetic coupling strongly depend on the molecule orientation with respect to the surface and the voltage polarity. Further analysis shows that this behavior is attributable to the stabilization/destabilization of the d-type singly occupied orbitals of the iron centers, reinforced by the strong local electric fields and induced charge densities only present in certain orientations of the deposited molecule and applied voltage polarity. © 2024 The Royal Society of Chemistry.